Econometric analysis of cross section and panel data - Wooldridge, Jeffrey M. (Cambridge, Mass. : MIT Press, 2002)
The book focuses specifically on cross section and panel data methods. It also clarifies the distinction between causality and statistical association.
Includes bibliographical references (p. [721]-735) and index.
osa 25/04/13
Loan
Keywords: Econometrics